Optimising antimicrobial stewardship interventions in English primary care: a behavioural analysis of qualitative and intervention studies. Issue 12 (17th December 2020) - Borek, Aleksandra J.; Wanat, Marta; Atkins, Louise; Sallis, Anna; Ashiru-Oredope, Diane; Beech, Elizabeth; Butler, Christopher C.; Chadborn, Tim; Hopkins, Susan; Jones, Leah; McNulty, Cliodna A. M.; Roberts, Nia; et al.
Abstract : Objective: While various interventions have helped reduce antibiotic prescribing, further gains can be made. This study aimed to identify ways to optimise antimicrobial stewardship (AMS) interventions by assessing the extent to which important influences on antibiotic prescribing are addressed (or not) by behavioural content of AMS interventions. Settings: English primary care. Interventions: AMS interventions targeting healthcare professionals' antibiotic prescribing for respiratory tract infections. Methods: We conducted two rapid reviews. The first included qualitative studies with healthcare professionals on self-reported influences on antibiotic prescribing. The influences were inductively coded and categorised using the Theoretical Domains Framework (TDF). Prespecified criteria were used to identify key TDF domains. The second review included studies of AMS interventions. Data on effectiveness were extracted. Components of effective interventions were extracted and coded using the TDF, Behaviour Change Wheel and Behaviour Change Techniques (BCTs) taxonomy. Using prespecified matrices, we assessed the extent to which BCTs and intervention functions addressed the key TDF domains of influences on prescribing. Results: We identified 13 qualitative studies, 41 types of influences on antibiotic prescribing and 6 key TDF domains of influences: 'beliefs about consequences', 'social influences', 'skills', 'environmental context and resources', 'intentions' and 'emotions'. We identified 17 research-tested AMS interventions; nine of them effective and four nationally implemented. Interventions addressed all six key TDF domains of influences. Four of these six key TDF domains were addressed by 50%–67% BCTs that were theoretically congruent with these domains, whereas TDF domain ' skills' was addressed by 24% of congruent BCTs and 'emotions' by none. Conclusions: Further improvement of antibiotic prescribing could be facilitated by: (1) national implementation of effective research-tested AMS interventions (eg, electronic decision support tools, training in interactive use of leaflets, point-of-care testing); (2) targeting important, less-addressed TDF domains (eg, ' skills ', 'emotions ' ); (3) using relevant, under-used BCTs to target key TDF domains (eg, 'forming/reversing habits', 'reducing negative emotions', 'social support'). These could be incorporated into existing, or developed as new, AMS interventions.